Adult Learning and Education in Ecuador and Peru: A fundamental need in the context of Human Mobility, during the period 2017-2019 (Praxis Educativa, 2023)
Faced with the massive displacement of approximately 4.5 million Venezuelans who move from their native country to different countries in Latin America and the world, between the years 2017-2019, Ecuador and Peru are located, respectively, as the third and second countries in reception of this population in a situation of human mobility. In this sense, the focus of interest of the States involved and of the international community is directed towards the urgency of carrying out comprehensive responses that address the various needs experienced by this population in relation to the guarantee of their fundamental human rights, particularly of the right to education throughout life. For this reason, this article analyzes the needs, regarding the right to Learning and Adult Education AEA, of the population in a situation of human mobility in Ecuador and Peru, during the period 2017-2019. Methodologically, this article pursues a descriptive scope, assumes a mixed research approach: qualitative-quantitative, is carried out on the basis of documentary analysis or theoretical perspective and applies the comparative method. As main results it is obtained that: the AEA is one of the fundamental rights least attended by the States, in terms of educational public policies; at least 70,000 people in Ecuador and 2,000 people in Peru, of Venezuelan nationality, would require AEA services; The AEA is problematized as a fundamental need for the Venezuelan population in a situation of human mobility in Ecuador and Peru, as it represents a right that enables the exercise of many others, as well as fundamental freedoms, during the period 2017-2019.
Keywords: Adult Learning and Education, Human Mobility, Fundamental Human Rights; Ecuador, Peru.